2011
DOI: 10.1364/oe.19.017092
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic coupling of silver nanoparticles covered by hydrogen-terminated graphene for surface-enhanced Raman spectroscopy

Abstract: We report on strong plasmonic coupling from silver nanoparticles covered by hydrogen-terminated chemically vapor deposited single-layer graphene, and its effects on the detection and identification of adenine molecules through surface-enhanced Raman spectroscopy (SERS). The high resistivity of the graphene after subjecting to remote plasma hydrogenation allows plasmonic coupling induced strong local electromagnetic fields among the silver nanoparticles to penetrate the graphene, and thus enhances the SERS effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…(10)] so that both the initial and the first intermediate states must be occupied implying that i = k = HOMO. However, in such a case, both denominators would be off resonance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(10)] so that both the initial and the first intermediate states must be occupied implying that i = k = HOMO. However, in such a case, both denominators would be off resonance.…”
Section: Discussionmentioning
confidence: 99%
“…However, as it was experimentally observed originally in 2010 by Ling et al [1], the Raman intensity of phthalocyanine, rhodamine 6G, protoporphyrin IX, and crystal violet molecules all have very different enhancement factors. Furthermore, it has been shown that enhancement factors are strongly dependent on which molecule is being probed, on the laser excitation energy used, on the two-dimensional (2D) material used for the enhancement surface [8][9][10] and even on the Fermi energy of the system, as controlled by a gate voltage [6,11,12]. The dependence of the enhancement on all these parameters cannot be explained either in terms of multiple reflections, nor by the quenching of the luminescence, nor even by a combination of both.…”
Section: Introductionmentioning
confidence: 99%
“…The substrate temperature 6 during the synthesis of graphene is measured to be in the range of 700~800℃. Gas pressure in the growth reactor is kept at 120Torr throughout the synthesis of the diamond film and graphene nanowalls.…”
Section: Methodsmentioning
confidence: 99%
“…Among them, carbon nanotube (CNT), carbon nanowalls, graphene, graphite, and diamond films are most studied for practical applications which demand good electrical conductivity besides a variety of outstanding physical and chemical properties [1][2][3][4][5][6][7][8]. Among promising applications, durable electrochemical electrode displaying a low background current in a wide potential window is an example.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation